Therapeutic implications of functional tea ingredients for ameliorating inflammatory bowel disease: a focused review. Issue 19 (28th October 2022) - Huang, Yina; Xing, Keyu; Qiu, Liang; Wu, Qinglong; Wei, Hua
Abstract: Inflammatory bowel disease (IBD) is a chronic gastro-intestinal disorders of unknown etiology. There are several drugs approved for treating IBD patients with active disease, including first-line use of aminosalicylates, and secondary choices of immunomodulators and other therapies. These medications might manage disease symptoms, but have also shown significant side-effects in IBD patients. Tea is the second largest beverage in the world and its main active ingredients including tea polyphenols, polysaccharides and tea pigments have been shown promising anti-inflammatory and antioxidant properties. In this review, we summarize the influence of different tea varieties including green tea, black tea and dark tea as potential nutritional therapy for preventing and treating IBD, and discuss the mechanisms of tea ingredients involved in the regulation of oxidative stress, inflammation, signaling pathways, and gut microbiota that could benefit for IBD disease management. Our observation directs further basic and clinical investigations on tea polyphenols and their derivatives as novel IBD therapeutic agents.